Environment Effect on the Rutting Resistance of Nano-SiO2-Modified Asphalt Concrete: Temperature and Water - Luchuan Chen; Wenjun Gu; Xuanyu Zhang (Advances in Civil Engineering)
Nanoparticles have been widely adopted to improve the high-temperature performance of asphalt binder. However, the influence of moisture on high-temperature performance is not clear. Hence, the water absorption performance of the nano-SiO2-modified asphalt concrete is investigated. Based on this, to further analyze the pavement performance of the nano-SiO2-modified asphalt concrete, the coupled effects of high-temperature, moisture content, and nanoparticles content on the rutting resistance of the nano-SiO2-modified asphalt concrete are tested and revealed in this study. Results show that temperature has the most significant influence on the water absorption performance of the nano-SiO2-modified asphalt concrete. The rutting resistance of the nano-SiO2-modified asphalt concrete decreases as temperature and moisture content increase, especially for the temperature. The dynamic stability at the same temperature condition decreases approximately linearly as moisture content increases. The effect of the nano-SiO2 content is the most nonobvious.